Driving effect of government environmental protection expenditure on green technology from the perspective of fiscal transparency - Chao Zhou; Min Li; Yunting Zhao (Humanities & Social Sciences Communications)
Abstract Green technology is crucial for achieving sustainable and high-quality development. Government environmental protection expenditure and fiscal transparency are key drivers of this process. Utilizing panel data from 254 Chinese cities between 2013 and 2020, this paper applies a panel least squares method with robust standard errors to explore the impact of government environmental protection expenditure on green technology, focusing on the role of fiscal transparency. The results reveal that fiscal transparency significantly moderates this relationship, a finding that withstands a series of robustness tests. Furthermore, the impact varies significantly across regions with different economic statuses and cities at various administrative levels. Fiscal transparency fosters the advancement of green technology by improving institutional frameworks, boosting corporate confidence, and increasing social investment, thereby enhancing green technology development through both government and social investment. Accordingly, it is recommended that the Chinese government emphasize the moderating effect of fiscal transparency on the impact of government environmental protection expenditure on green technology and implement effective strategies to reduce excessive regional disparities in these effects. Moreover, by enhancing fiscal transparency, the government should enhance the contribution of social capital to green technology development.